Ocean acidification and the Permo-Triassic mass extinction. - Clarkson, MO; Kasemann, SA; Wood, RA; Lenton, TM; Daines, SJ; Richoz, S; Ohnemueller, F; Meixner, A; Poulton, SW; Tipper, ET (American Association for the Advancement of Science (AAAS), 2015)
Ocean acidification triggered by Siberian Trap volcanism was a possible kill mechanism for the Permo-Triassic Boundary mass extinction, but direct evidence for an acidification event is lacking. We present a high-resolution seawater pH record across this interval, using boron isotope data combined with a quantitative modeling approach. In the latest Permian, increased ocean alkalinity primed the Earth system with a low level of atmospheric CO2 and a high ocean buffering capacity. The first phase of extinction was coincident with a slow injection of carbon into the atmosphere, and ocean pH remained stable. During the second extinction pulse, however, a rapid and large injection of carbon caused an abrupt acidification event that drove the preferential loss of heavily calcified marine biota.